The solution of an open XXZ chain with arbitrary spin revisited. (3rd February 2015) - Murgan, Rajan; Silverthorn, Chris
Abstract: The Bethe ansatz solutions for an open XXZ spin chain with arbitrary spin with N sites and nondiagonal boundary terms are revisited. The anisotropy parameter, for cases considered here, has values, where r and q are positive integers with q restricted to odd integers. Numerical results are presented to support the solutions.